Targeted next‐generation sequencing in a large series of fetuses with severe renal diseases. Issue 3 (10th January 2022) - Jordan, Penelope; Dorval, Guillaume; Arrondel, Christelle; Morinière, Vincent; Tournant, Carole; Audrezet, Marie‐Pierre; Michel‐Calemard, Laurence; Putoux, Audrey; Lesca, Gaethan; Labalme, Audrey; Whalen, Sandra; Loeuillet, Laurence; et al.
Abstract: We report the screening of a large panel of genes in a series of 100 fetuses (98 families) affected with severe renal defects. Causative variants were identified in 22% of cases, greatly improving genetic counseling. The percentage of variants explaining the phenotype was different according to the type of phenotype. The highest diagnostic yield was found in cases affected with the ciliopathy‐like phenotype (11/15 families and, in addition, a single heterozygous or a homozygous Class 3 variant in PKHD1 in three unrelated cases with autosomal recessive polycystic kidney disease). The lowest diagnostic yield was observed in cases with congenital anomalies of the kidney and urinary tract (9/78 families and, in addition, Class 3 variants in GREB1L in three unrelated cases with bilateral renal agenesis). Inheritance was autosomal recessive in nine genes ( PKHD1, NPHP3, CEP290, TMEM67, DNAJB11, FRAS1, ACE, AGT, and AGTR1 ), and autosomal dominant in six genes ( PKD1, PKD2, PAX2, EYA1, BICC1, and MYOCD ). Finally, we developed an original approach of next‐generation sequencing targeted RNA sequencing using the custom capture panel used for the sequencing of DNA, to validate one MYOCD heterozygous splicing variant identified in two male siblings with megabladder and inherited from their healthy mother.